A history of horror - Dixon, Wheeler W., 1950- (New Brunswick, New Jersey : Rutgers University Press, 2010)
Ever since horror leapt from popular fiction to the silver screen in the late 1890s, viewers have experienced fear and pleasure in exquisite combination. A History of Horror, with rare stills from classic films, is the only book to offer a comprehensive survey of this ever-popular film genre. Chronologically examining over fifty horror films from key periods, this one-stop sourcebook unearths the historical origins of legendary characters and explores how the genre fits into the Hollywood studio system and how its enormous success in American and European culture expanded globally over time.--
Origins : 1896-1929 -- Classics : 1930-1948 -- Rebirth : 1949-1970 -- New blood : 1970-1990 -- The future : 1990-present -- Top horror web sites -- 50 classic horror films.
Includes bibliographical references, webliography, and filmography (pages 211-222) and index.
Print version record.
In English.
JSTOR
Keywords: Horror films -- History and criticism; Films d'horreur -- Histoire et critique; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Horror films; Electronic books; Criticism, interpretation, etc